Laparoscopic transabdominal preperitoneal versus open mesh lichtenstein repair of inguinal hernia: a comparative analysi - Akhtar, Mohammad Sadik; Mohammad Ali, Wasif; Ahmed Khan, Tausif; Raza, Mohammad Habib; Ahmad, Manzoor; Sajid, Mohammad (International Journal of Medical Research and Review, 2016)
Background: Inguinal hernia repair is a commonly performed surgery usually managed by open surgical mesh repair. Nowadays many patients are demanding laparoscopic hernia repair. Laparoscopic hernioplasty has a shorter rehabilitation, but it is a technically difficult procedure. It is unclear if it has advantages over open tension-free mesh repair. Methodology: This prospective study of 80 patients is done at Jawaharlal Nehru Medical College Hospital, A.M.U., Aligarh from January 2012 to November, 2014. 50 patients underwent Lichtenstein tension free mesh repair while on 30 patients TAPP was performed. Results: Out of 80 patients 7 patients were lost to follow up at 2 weeks. 47 patients in Lichtenstein group and 26 patients in TAPP group were followed for 6 months. Average operation time was 39.3±16.4 minutes for the Lichtenstein group and 51.4±15.8 minutes for the TAPP group. Postoperatively, pain score was 6.5±3.5 in lichtenstein group as compared to 5.8±1.5 in TAPP group. Because of lesser postoperative pain, the TAPP patients got significantly fewer analgesics than the Lichtenstein patients (2.4 ± 1.0) versus (3.5 ± 1.3) doses. TAPP patients needed significantly fewer admission days than Lichtenstein patients (2.5±0.6 versus 1.8±0.5 days, respectively). TAPP patients returned to work earlier as compared to Lichtenstein group (11.7±4.9 days versus 14.8±4.2 days respectively). Short term and long complications were similar in both groups. Conclusion: Laparoscopic hernioplasty (TAPP) is superior to Lichtenstein tension-free hernioplasty in terms of postoperative pain, hospital stay and return to daily activity.